Learning Obtacles for Junior High School Students on The Concept of Quadratic Equations - Wafa Islamiyah; Didi Suryadi; Sufyani Prabawanto; M Akbar Gulvara (Mathematics Education Study Program, 2023)
This research aims to identify the learning obstacles faced by students in the topic of quadratic equations. The data for this study were obtained through tests and interviews. A qualitative research method with a hermeneutic phenomenology design was employed. The study involved 30 ninth-grade students from a junior high school in Banjar Regency, South Kalimantan. Several learning obstacles were experienced by students in the concept of quadratic equations, namely: 1) ontogenic obstacles occur due to students' inability to grasp the concept of quadratic equations. This is caused by a mismatch between the learning or knowledge intended to be constructed by students and their thinking abilities; 2) Didactical obstacles arise from the lack of coherence in the material, both in terms of the interconnectedness of quadratic equation concepts and the continuity of the thinking process, as well as the presentation of less-detailed materials; 3) Epistemological obstacles occur because students' knowledge related to quadratic equations is limited to specific contexts only.